The Strategy of the Madrasah Principal in Shaping Image through Public Relations Management - Yasin, M.; Nur, Muhammad Amin (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2025)
In an increasingly competitive educational landscape, institutions are leveraging technology and social media to enhance their public image, build trust, and establish strong branding. This qualitative study explores the strategic role of the principal in managing public relations (PR) to shape a positive institutional image at Madrasah Tsanawiyah Al-Yasini. Through observations and interviews with the principal and PR team, the research underscores the centrality of the principal’s leadership in directing and evaluating PR performance. The study adopts the Four-Step PR Model—Problem Defining, Planning, Implementation, and Evaluation—as an analytical framework. Findings reveal that the principal’s strategy is effectively realized through flagship programs such as the Genius Class and scholarship initiatives, as well as the formation of a specialized PR IT Team. These efforts led to a notable increase in student enrollment, reflecting improved institutional visibility and reputation. However, challenges persist in the form of inconsistent content posting, subpar visual presentation, and limited creativity in digital communication. The study concludes that while strategic leadership is a critical enabler of successful PR, there is a pressing need to enhance the technical and creative capacities of the PR team to fully leverage digital platforms and sustain institutional growth.